The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s004170100360
|View full text |Cite
|
Sign up to set email alerts
|

Adventitial sheathotomy for decompression of recent onset branch retinal vein occlusion

Abstract: although feasible, sheathotomy did not lead to a significant visual improvement in our patients. Dissection of the arteriovenous crossing could have induced vascular trauma. Furthermore, vitrectomy with posterior hyaloid detachment alone could be of benefit in the treatment of branched retinal vein occlusions. A prospective randomised trial is needed to assess the effectiveness and the safety of this procedure and to determine the best candidates for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…This has been expressed by authors reporting results of sheathotomy. [8][9][10][11][12][13][14][15][16] The possibility of rupture of one of the vessels may be frightening and dissuasive for surgeons. What should be known is whether this new surgical procedure is worth performing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been expressed by authors reporting results of sheathotomy. [8][9][10][11][12][13][14][15][16] The possibility of rupture of one of the vessels may be frightening and dissuasive for surgeons. What should be known is whether this new surgical procedure is worth performing.…”
Section: Discussionmentioning
confidence: 99%
“…To analyse and compare the studies on sheathotomy is difficult because of differences and variations of methodology. [8][9][10][11][12][13][14][15][16][21][22][23][24][25][26][27][28][29][30] No control group that has similar conditions could have been created in the majority of the reported studies. Some case reports have shown favourable results while others have not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decompression at the arteriovenous crossing site can theoretically be effective in treating the pathogenetic mechanism by improving the venous blood flow. Even though the data are not univocal, overall, the majority of the reports have suggested that this surgical approach is beneficial in improving VA and reducing ME [75,76,77,78]. Nevertheless, some studies comparing vitrectomy alone with vitrectomy associated with sheathotomy have pointed out the absence of any difference in the clinical outcomes [79, 80].…”
Section: Treatmentmentioning
confidence: 99%
“…Several small, uncontrolled series have shown good results in improving macular edema and macular perfusion. However, others have reported a lack of efficacy of this procedure (Le Rouic et al, 2001;Cahill et al, 2003).…”
Section: Management Of Branch Retinal Vein Occlusionmentioning
confidence: 99%